EFFECT OF APPLICATION METHODS OF PLANT GROWTH STIMULANTS ON GROWTH AND YIELD OF SNAP BEAN - A.M. Shaheen; E.H. Abd El-Samad; F.A. Rizk; A.G. Behairy; S.M. Adam (Journal of Animal and Plant Sciences, 2018)
Plant growth stimulants have the potential to enhance plant growth and productivity as well as improve the plants adaptive/resistance to environmental stressors, particularly in newly reclaimed areas. Therefore, two field experiments were conducted during seasons of 2014/2015 and 2015/2016 under newly reclaimed sandy soil conditions at the Experimental and Production Station of National Research Centre, El-Noubaria region, Behera governorate, Egypt. In order to investigate the effect of application methods, pre-sowing seed soaking for 6 h or foliar spraying for three times starting at 15 days after seeding in 10 days interval on the efficiency of plant growth stimulants (amino acids 2.5 ml/l, IAA 150 ppm and GA 50 ppm as well as control treatment) on growth, yield and quality of snap bean cv. Paulista. The 3 experiments were laid out in a split plot design with 3 replicates. The obtained results revealed that foliar spraying of plant growth stimulants was superior than seed soaking in improvement of plant vegetative growth parameters. Also, it gained the highest values of total pods yield as g/plant or ton/ha and pod physical characters in relative to seed soaking method. Moreover, it was evident that the application methods had no significant effect on the nutritional values of bean pods, except for K in the first season and Fe content in both seasons. Plant growth stimulants positively increased plant vegetative growth, pod yield and pod quality attributes over control treatment in both seasons. GA (50 ppm) 3 significantly increased plant vegetative growth, total pods yield (g/plant or ton/ha) and pod physical properties followed by amino acids treatment (2.5 ml/l) without significant differences between them. On the other hand, amino acids treatment gave the highest nutritional values of protein, N, P and K, while, the highest values of Fe, Mn, Zn and Cu contents were attained by GA treatment. The interaction effect had significant differences on most of measured 3 parameters during both seasons of study. The most effective treatment was GA (50 ppm) as foliar spraying on vegetative 3 growth, total pods yield and yield attributes as well as amino acids (2.5 ml/l) even as foliar spraying or seed soaking on pod nutritional values. 3 quality. account, the environmental risks which threatened human
Keywords: Snap bean; Seed soaking; Foliar spraying; GA; IAA; Amino acids; Plant vegetative growth; Pods yield and